2019
DOI: 10.18632/oncotarget.26863
|View full text |Cite
|
Sign up to set email alerts
|

Differential microglia and macrophage profiles in human IDH-mutant and -wild type glioblastoma

Abstract: Microglia and macrophages are the largest component of the inflammatory infiltrate in glioblastoma (GBM). However, whether there are differences in their representation and activity in the prognostically-favorable isocitrate dehydrogenase (IDH)-mutated compared to -wild type GBMs is unknown. Studies on human specimens of untreated IDH-mutant GBMs are rare given they comprise 10% of all GBMs and often present at lower grades, receiving treatments prior to dedifferentiation that can drastically alter microglia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 55 publications
5
45
0
Order By: Relevance
“…However, most studies show that, despite being well tolerated, immunotherapy failed to prolong GBM patient survival [ 149 ], perhaps because it focused on T-cells, which are sparse in GBM [ 150 , 151 , 152 ]. More recently, an association between the IDH1/2 mutations profile and the macrophagic subsets in GBM has pointed to macrophages and microglia as useful players in new immunotherapeutic approaches [ 153 ].…”
Section: Malignant Gliomas a Therapeutic Challengementioning
confidence: 99%
“…However, most studies show that, despite being well tolerated, immunotherapy failed to prolong GBM patient survival [ 149 ], perhaps because it focused on T-cells, which are sparse in GBM [ 150 , 151 , 152 ]. More recently, an association between the IDH1/2 mutations profile and the macrophagic subsets in GBM has pointed to macrophages and microglia as useful players in new immunotherapeutic approaches [ 153 ].…”
Section: Malignant Gliomas a Therapeutic Challengementioning
confidence: 99%
“…Surrounding BTICs in situ are microglia, which are innate immune cells of the CNS and macrophages that have infiltrated as monocytes from the circulation (13)(14)(15)(16). These cells are thought to be initially recruited to eradicate the tumor by stimulating apoptosis of glioma cells (17) and by secreting inflammatory factors that prevent glioma growth and invasiveness (18).…”
Section: Introductionmentioning
confidence: 99%
“…Literature review showed a computational approach named correlation-based feature subset (CFS) identified TYROBP as part of the hub genes in kidney cancer samples using protein-protein interaction network 63 . Another study reported that microglia in IDH-mutants are mainly pro-inflammatory, while anti-inflammatory macrophages that upregulate genes such as FCER1G and TYROBP predominate in IDH-wild type GBM 64 . Tyrobp and Fcer1g was found to be differentially expressed in Alzheimer’s disease (AD) mouse models that demonstrated strong correlation between cortical Aβ amyloidosis and the neuroinflammatory response 65 .…”
Section: Discussionmentioning
confidence: 99%